Kroparski vzdevki - Škofic, Jožica (Traditiones (Ljubljana), 2000)
The article looks at nicknames from Kropa and their phonetical and syntactical characteristics. The author also analyzes various motifs for their origin which reveal the unusual linguistic wealth of this Gorenjsko town
Keywords: linguistics; jezikoslovje; slovenščina; Slovene; Slovene dialects; slovenska narečja; Kropa; kroparski govor; vzdevki